Assessing food security among U.S. post-secondary level students - Bobadilla Suero, Jeimy (My University, 2025)
The prevalence of food insecurity among college and university students in the United States ranges from 19% to 52%, which is significantly greater than the national average. In this context, this study aims to determine the prevalence of food insecurity among students from higher education and examine if sociodemographic factors such as income, race, sex, marital status, and parental status significantly predict levels of food security. This study used data from the Current Population Survey (CPS), administered by the U.S. Census Bureau, comprising 22,686 students from 2019–2023 across the United States. This investigation used the Food Security Index using the 10-item U.S. Adult Food Security Survey Module developed by the United States Department of Agriculture (USDA). Furthermore, a generalized linear model was employed to examine the relationship between multiple demographic factors and food security, with model selection based on Akaike’s Information Criterion (AIC). The best-fit model included all predictor variables: income, race, age, sex, marital status, and parental status. However, the model demonstrated moderate predictive power (R² = 0.07). Contrary to much of the existing literature, 12% of college students in our sample experienced food insecurity. Multiethnic and Black students reported greater levels of food insecurity compared to White and Asian students, with Multiethnic students nearly being two times more food insecure than their White peers. Students with parental responsibilities are approximately 1.55 times more likely to experience food insecurity than their peers without children. Female and older students also experienced higher levels of food insecurity, whereas greater household income was associated with increased food security. Married and never-married students exhibited lower levels of food insecurity than those whose marital status is separated, widowed, or divorced. Given that a sizable proportion of the variance remains unexplained, further research is needed to identify additional factors influencing food security in this population. Nonetheless, this study provides a valuable benchmark for future research investigating more fine-grained demographic questions related to food security among post-secondary level students across the U.S.
Keywords: Food security; Students; U.S. post-secondary level